Implementation of Collateral-Based Financial Management in BLM-PUAP in Gapoktan Bangunsari Madiun - Masruroh, Yulian (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This study discusses the financial management of Community Direct Assistance - Rural Agribusiness Business Development (BLM-PUAP) in Bangunsari Village, Dolopo District, Madiun Regency, using a qualitative approach and inductive descriptive methods. Data were collected through observations, in-depth interviews, and documentation to describe in detail the implementation of financial management in the Gapoktan. The results of the study show that financial management has been carried out in accordance with PUAP guidelines, including the preparation of the Revenue and Expenditure Budget Plan (RAPB) and the provision of loans to members and the community. After a few years, the non-collateral system poses obstacles such as bad loans, so a collateral-based system is implemented, where the collateral value must be greater than the loan, and the 5C principle is used in financing analysis to reduce the risk of bad loans. This implementation helps keep the annual burden below 50% and the credit congestion rate below 20%, as well as improve the reliability of the organization's financial management. It is proven that the implementation of collateral-based financial management has a positive impact on the financial stability of Gapoktan Bangunsari.